Enzymology at the membrane interface - intramembrane proteases - Gelb, Michael H. (Methods in enzymology, 2017)
Enzymology at the Membrane Interface: Intramembrane Proteases, Volume 584,the latest release in the Methods in Enzymology series, covers a subset of enzymes that work in the environment of the biological cell membrane. This field, called interfacial enzymology, involves a special series of experimental approaches for the isolation and study of these enzymes.Covers a subset of enzymes that work in the environment of the biological cell membraneOffers a series of experimental approaches for the isolation and study of enzymes
Keywords: Aufsatzsammlung; Wechselwirkung; Biomembran; Proteasen